Comparison of pain observed with sodium hypochlorite and chlorhexidine based root canal irrigant 24 hours post appointment - Amjad, Sadaf; Afreen, Zarah; Afreen, Ammarah; Shuja, Eruj; Rasheed, Hassan; Rashid, Sundus (Journal of Rawalpindi Medical College, 2022)
Objective: To compare the effectiveness of 2.5% sodium hypochlorite and 2% chlorhexidine, in reduction of frequency in pain 24 hours after endodontic treatment of teeth with chronic apical periodontitis Study design and Setting: Randomized Clinical Trial conducted –removed for blind review--from July 2018 to December 2018. Methodology: A total of 60 patients requiring management of chronic apical periodontitis and pulp necrosis were randomly allocated by lottery method to two groups of 30 each according to the irrigating solution employed: Group A (2.5% sodium hypochlorite) or Group B (2% chlorhexidine gluconate). To assess inter-appointment pain, a questionnaire with visual analogue scale was filled out by the patient at 24 hours after the procedure. The Chi-square test was used to compare the effectiveness between the two irrigation solutions. Results: Group A (2.5% sodium hypochlorite) was effective in 83.3% cases i.e. no or mild pain compared to 76.7% in group B (2% chlorhexidine). In group A, 5(16.7%) patients suffered pain compared to 7(23.3%) in group B. This difference in pain was statistically insignificant. (p-value 0.519). Conclusion: Both 2.5% sodium hypochlorite and 2% chlorhexidine were equally effective in minimizing pain 24 hours post endodontic treatment. Keywords: Chlorhexidine gluconate, Sodium hypochlorite, Flare up